PERBEDAAN BODY DISSATISFACTION PADA PEREMPUAN DI USIA REMAJA DAN DEWASA AWAL PENGGUNA INSTAGRAM - Wahyuni, Wahyuni; Widyarini, Nilam; Budi Setyawan, Aris (Lafadz Jaya Publisher, 2024)
Body dissatisfaction is more common in women during puberty and early adulthood. where appearance becomes more important in society, this raises a question about whether there is a difference in women experiencing body dissatisfaction in adolescence and early adulthood. This study used non-probability sampling using purposive sampling techniques, and body dissatisfaction measurements were arranged based on aspects proposed by Cash (2000), the population in this study were late adolescent women aged 19-22 years and early adults aged 23-30 years, residing in Jakarta, Bogor, Depok, Tangerang or Bekasi, and using Instagram social media. This study used quantitative analysis of different tests using the independent sample test statistical technique to determine the differences and statistical analysis of the t-test used for testing on body dissatisfaction and the developmental stages of adolescence and early adulthood (the results are further explained) with the help of IBM SPSS for Windows version 25. The results of this study indicate that there is a significant difference in body dissatisfaction in women in adolescence and early adulthood who use Instagram.